2020
DOI: 10.7717/peerj.10021
|View full text |Cite|
|
Sign up to set email alerts
|

No Mow May lawns have higher pollinator richness and abundances: An engaged community provides floral resources for pollinators

Abstract: No Mow May is a community science initiative popularized in recent years that encourages property owners to limit their lawn mowing practices during the month of May. The goal of No Mow May is to provide early season foraging resources for pollinators that emerge in the spring, especially in urban landscapes when few floral resources are available. We worked with the city council of Appleton, Wisconsin, USA. to allow No Mow May to take place in May 2020. Four hundred and thirty-five property owners registered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…This is consistent with a meta-analysis by Winfree et al [ 20 ] who found that habitat fragmentation significantly negatively influenced bee populations, when in systems with little natural habitat remaining. Urban spaces managed for pollinator conservation can alleviate this negative influence, by providing a variety of habitat and floral resources for bees, which is supported by this study and other recent work on urban bee populations [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with a meta-analysis by Winfree et al [ 20 ] who found that habitat fragmentation significantly negatively influenced bee populations, when in systems with little natural habitat remaining. Urban spaces managed for pollinator conservation can alleviate this negative influence, by providing a variety of habitat and floral resources for bees, which is supported by this study and other recent work on urban bee populations [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 79%
“…Similar to prior studies, no‐mow was found to yield greater nectar sugar resource and gamma richness of open flower species compared to standard mowing (cf. Del Toro & Ribbons, 2020; Lerman et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The decline in pollinator abundance has been attributed, in part, to reduced pollen and nectar resource (Powney et al., 2019). No‐mow has been proven to very effectively increase early season floral abundance and richness in domestic lawns, which in turn support a greater abundance and/or richness of bees (Del Toro & Ribbons, 2020; Lerman et al., 2018; Wastian et al., 2016). Floral abundance has been used as a proxy measure for pollinator resource, but the availability of U.K. wildflower nectar values has since enabled more precise quantification (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Urban ecologists are increasingly encouraging the conversion of traditional monoculture turfgrass lawns to more diverse habitats (e.g., [2,37]). Millions of citizens engage in ecological gardening and landscaping to support pollinators [38,39], and there is a growing public acceptance of flowering lawns in community parks [40] and residential yards [41][42][43].…”
Section: Introductionmentioning
confidence: 99%